MULTIPLE SCLEROSIS-AYURVEDIC MANAGEMENT AND PREVENTIVE ASPECTS - Sasikumar, *Arjun; M, Aswathy (International Journal of Ayurveda and Pharma Research, 2018)
Multiple Sclerosis (MS) is a chronic progressive disease with a variety of cognitive, motor and sensory deficits. It is characterised by demyelination of axons of the brain and spinal cord where the patient presents with the complaints of blurred or double vision, lack of coordination, loss of balance, numbness and tremors throughout the body or extremities with weakness, muscle spasms etc. In Ayurveda, Multiple Sclerosis can be correlated to Snayusada or the aggravation of Vata in Snayu. Modern treatments like immunosuppressant, corticosteroids, stem cell therapy are highly expensive when compared to Ayurvedic management. The scope of Ayurvedic Management and preventive aspects mainly concentrates on improving the quality of life and decrease dependency of patients. The objective of this review is to evaluate the clinical utility of the Ayurvedic medicines for Multiple Sclerosis. Clinical trials by Ayurvedic experts suggest that Ayurvedic treatment processes and preventive measures (Life style management and recommended diet) may reduce the risk of Multiple Sclerosis. Here I briefly explain the current literature of Multiple Sclerosis, modern and Ayurvedic views, Ayurvedic medicines usually given in Multiple Sclerosis cases with a focus on designing prevention and treatment protocol.